León Grinberg y Rebeca Grinberg. Psicoanálisis de la migración y del exilio. Madrid : Alianza, 1984. 272 p. - Hodara B., Joseph (Estudios Demográficos y Urbanos, 1986)
LEÓN GRINBERG Y REBECA GRINBERG. Psicoanálisis de la migración y del exilio. Alianza, Madrid, 1984.